Preliminary Evaluation for Major Health Risks of Heavy Metals in Drinking Water Sources of Huainan City in China - Cui, Hongshan; Zhou, Bohan (Asian Journal of Chemistry, 2015)
In this paper, the authors have investigated main concentration of heavy metal pollutants in drinking water in the urban area of Huainan city of China. The source of health risks of heavy metals in drinking water is also evaluated. The monitoring results revealed that carcinogens of health risk is higher whereas the chromium in a waterworks intake of personal annual average risk degree is the highest at 7.527 × 10-5 a-1. Part time index is higher than that of the United States Environmental Protection Agency (USEPA) and the International Radiation Protection (ICRP) Committee. Heavy metal Hg, Pb, Cu , Zn and Tl in drinking water causes non-carcinogenic average annual health risk value as 10-12 a-1-10-9 a-1 which is far below the International Commission on Radiation Protection (ICRP) recommended level as (5 × 10-5 a-1).